THE EFFECT OF PROFITABILITY, LEVERAGE, COMPANY SIZE AND CORPORATE SOCIAL RESPONSIBILITY ON EARNING RESPONSE COEFFICIENT IN HEALTH COMPANIES - Siti Ikrimatul Auliya; Laely Aghe Africa (Universitas Maarif Hasyim Latif, 2023)
This study aims to determine whether profitability, leverage, company size and corporate social responsibility affect the earning response coefficient in health companies. This study uses the dependent variable, namely earning response coefficients which calculated by proxy of regression between accounting profit and stock prices, and the independent variable is profitability as proxy of Return On Assets. (ROA), leverage as proxy of Debt to Equity Ratio (DER), company size as proxy of natural logarithm of total assets (SIZE) and corporate social responsibility as measured using the GRI4 indicator. Secondary data obtained from the Indonesia Stock Exchange (IDX) for the 2016-2020 period. With a population of health companies listed on the Indonesia Stock Exchange (IDX) with a sample of health companies for the 2016-2020 period. Sampling done using purposive sampling method, where the sample selected based on the criteria made by the researcher. The data analyzed by descriptive analysis techniques, classical assumption test and multiple linear regression analysis using SPSS 24. The results of this study indicate that profitability (PROF), Leverage (LEV) and firm size (SIZE) have no effect on earning response coefficient, while corporate social responsibility (CSR) has a negative effect on the earning response coefficient. Keywords: Earning response coefficient, Profitability, Leverage, Company Size, Corporate social responsibility